Faktor Penentu Praktik Keamanan Pangan pada Ibu Balita di Kelurahan Gedongkiwo, Mantrijeron, Yogyakarta - Arihni Arihatal Jannah; Dyah Suryani; Tri Wahyuni Sukesi (Jurnal Penelitian Pendidikan IPA, 2023)
Food safety is very important, and the implementation of effective food safety practices among mothers is very important in mitigating the incidence of foodborne diseases in the vulnerable age group of toddlers. This research aims to determine the factors that influence food safety practices among mothers of toddlers in Gedongkiwo Village, Mantrijeron, Yogyakarta. This research uses a quantitative approach with analytical observational methods and a cross-sectional research design. The research population consisted of all mothers of toddlers in Gedongkiwo Village, totaling 462 mothers and a sample of 215 mothers. The sampling method used was proportional stratified random sampling. For data collection, a questionnaire was used as a research instrument. Data analysis included descriptive statistics, chi-square analysis, and binary logistic regression. The results showed that education level and employment status were associated with a 0.373 and 0.415 higher likelihood, respectively, for mothers of toddlers to adopt food safety practices. Based on the results, it was concluded that employment status was the factor most related to food safety practices.